56 A nationwide survey of the attitudes of doctors and dentists in training towards the use of evidence-based practice. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Hong, Bosun; Jones, Christopher; ,
Abstract : Objectives: The use of best evidence is vital to improving patient outcomes. Whilst organisational adherence to the evidence-base has previously been studied, the extent to which trainee clinicians engage with evidence-base practice is unclear. We outline here the results of a national survey of medical and dental trainees from across the United Kingdom (UK) and the Republic of Ireland (RoI) that sought to determine the extent to which doctors and dentists in training use the evidence base in everyday clinical practice, and to evaluate barriers to further engagement. Method: A nationwide survey of medicine and dentistry trainees within the UK and RoI was undertaken by the Cochrane UK and Ireland Trainees Advisory group. An online questionnaire was developed using the SurveyMonkey cloud-based online survey programme and adapted following a pilot study of 16 trainees from a range of medical and dental specialties. The questionnaire was distributed to trainees across the UK and RoI via two routes between 19 September 2017 and 8 November 2017. Firstly, an online and social media strategy was employed to raise awareness of the survey. Secondly, the survey was highlighted to specialty and deanery-specific organisations who were asked to distribute it to trainees via mailing lists or ePortfolio accounts, including for instance the Foundation Programme national bulletin. Doctors and dentists were eligible for participation if they held a recognised UK or RoI training post at the time of survey completion. Results: The survey yielded 243 responses form 30 medical/surgical specialties and seven dental specialties. Approximately half (52.0%) of the respondents reported they referred to the literature at least weekly to determine the evidence base for a clinical decision. The foremost two barriers to evidence-based practice were insufficient time (54.6%) and tendency to follow the generally accepted clinical practice in their department (41.7%). In addition, 22.3% reported they would feel comfortable querying a colleague's management based on their understanding of relevant evidence only if that colleague was more junior/less experienced than them. The motivators to evidence-based practice included the desire to better understand how clinical decisions are made (61.6%) and senior encouragement (38.9%). When asked how they could be encouraged to draw more on the evidence base by Cochrane UK, the respondents expressed most interest in receiving email updates on evidence-based practice (53.7%) or participating in online journal clubs (47.3%). Conclusions: A lack of time, a reluctance to challenge colleague's management and the influence of established departmental practice are key inhibitors to the wider adoption of evidence-based practice by medical and dental trainees. Further work will be undertaken by the Cochrane UK and Ireland Trainees Advisory Group to challenge these barriers and improve trainee engagement with the evidence base.